Expectations of a winning result in women`s handball team: comparison of different age groups - Popovych, O.; Blynova, O.; Savchuk, O.; Zasenko, V. (Journal of Physical Education and Sport, 2020)
The aim of the article is an empirical study of the expectations of a winning result and its comparison in three age groups of women`s handball club "Dniprianka" (Kherson, Ukraine). Study participants are: senior age group (n = 16; 19-27 years) - Championship of Ukraine (Super League); middle age group (n = 11; 15-17 years old) - Championship of Ukraine (Junior League); youngerage group (n = 9; 13-15 years) - Championship of Ukraine (Children`s League). The influence of pre-start emotional states on the female handball players` expectations of a winning sports result is determined and substantiated. Methods. Clear of purpose observation, standardized and adapted psychodiagnostic methods with experimental scales, factor analysis by the method of principal components, rotation - Varimax are applied. Results. The influence of emotions "joy" and "interest" on the pregame expectations of handball players has been established. The connection of emotions with awareness of the foreseeable course of events, with the apprehended attitude to the participants of the game interaction, with the level of expected results from the game (p <.05) is determined.Factor analysis proved the existence of a set of variables aimed at the future outcome of the competition, as well as to obtain positive emotions from the game process, the desire to avoid defeat in a sports match. The differences between the female handball players of the main team and the female athletes of the youth and children`s teams in terms of emotional states and psychological content parameters of pre-game expectations (p <.05) were clarified. The factor structure of prestart emotional states of the winning result expectancy of handball players is constructed. The factor structure consists (68.82%): F1 "Expectation of a winning result" (34.72%); F2 "Expectation of positive emotions from the game process" (21.84%); F3 "Expectation of an opportunity to avoid defeat" (7.51%) and F4 "Expectation of a negative scenario" (4.75%). It is advisable to implement the obtained empirical results in the tactical psychological training of athletes in game sports.